Evaluation of Physiological and Orgaleptic Properties of Mango cv. Kesar as Influenced by Ionizing Radiation and Storage Temperature - Yadav, MK; Patel, NL; Parmar, BR; Nayak, Dileswar (SAARC Journal of Agriculture, 2014)
Radiation processing of fruits involves exposure to short wave energy to achieve a specific purpose to maintain the physiological changes and sensory quality of the product. The effect of gamma irradiation and storage temperature on physiological changes and organoleptic properties of mango fruit var. Kesar was studied. The fruits were exposed to gamma radiation at different doses i.e. 0.00kGy, 0.20kGy, 0.40kGy and 0.60kGy from the radio isotope 60Co and stored at different storage environments i.e. at ambient storage (27±2°Cwith 60-70% RH); at 9°C with 90% RH; at 12°C with 90% RH and control atmosphere storage ( at 12°C, O2 2%, CO2 3% and RH 90%). The fruits irradiated with 0.40kGy gamma rays and stored at 9°C storage temperature with 90% RH recorded maximum reduction in physiological loss in weight and reduced ripening. The minimum physiological loss in weight and ripening and highest marketability of fruits was recorded from fruits irradiated with 0.40kGy gamma rays and stored at 12°C storage temperature with 90 RH including maximum scores on skin colour, pulp colour, texture, taste and overall acceptability at the end of shelf life (41.43 days). DOI: http://dx.doi.org/10.3329/sja.v11i2.18403 SAARC J. Agri., 11(2): 69-80 (2013)